2021
DOI: 10.1111/efp.12680
|View full text |Cite
|
Sign up to set email alerts
|

Early infection by Phytophthora agathidicida up‐regulates photosynthetic activity in Agathis australis seedlings

Abstract: Kauri (Agathis australis (D.Don) Lindl.) has ecological, historical and cultural value to both indigenous and non-indigenous New Zealanders (Steward & Beveridge, 2010). Consequently, the decline of this species is having significant negative impacts on the already heavily fragmented kauri population (National (Kauri Dieback) Pest Management Plan, 2019). Phytophthora species are notorious invasive plant pathogens that have spread into new environments, where the hosts have little natural resistance, through glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Indeed, trees infected with P. plurivora showed increased rates of net photosynthesis compared to those infected with P. cactorum during the growing season following the inoculation, despite the differences being not significant in all measurement days ( Ďurkovič et al., 2021 ). To this regard, it has been suggested that infected tissues can act as a carbon sink, altering plant resource allocation patterns, which can be compensated by increased photosynthetic rates ( Pagán and García-Arenal, 2018 ; Berezovska et al., 2021 ; D’Souza et al., 2021 ). In fact, several carbohydrates, including sucrose, showed an increased concentration in areas surrounding the necrotic tissues ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, trees infected with P. plurivora showed increased rates of net photosynthesis compared to those infected with P. cactorum during the growing season following the inoculation, despite the differences being not significant in all measurement days ( Ďurkovič et al., 2021 ). To this regard, it has been suggested that infected tissues can act as a carbon sink, altering plant resource allocation patterns, which can be compensated by increased photosynthetic rates ( Pagán and García-Arenal, 2018 ; Berezovska et al., 2021 ; D’Souza et al., 2021 ). In fact, several carbohydrates, including sucrose, showed an increased concentration in areas surrounding the necrotic tissues ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%